Synthesis, Crystal Structure, and Catalytic Activity of a Calcium(II) Complex with 4-Formylbenzene-1,3-disulfonate-isonicotinic Acid Hydrazone - Xi-Shi Tai; Peng-Fei Li; Li-Li Liu (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2018)
A new calcium(II) complex was synthesized by one-pot synthesis method from disodium 4-formylbenzene-1,3-disulfonate, isonicotinic acid hydrazide and Ca(ClO4)2•2H2O. The structure of calcium(II) complex was determined by elemental analysis, IR and single crystal X-ray diffraction. The results show that the Ca(II) complex molecules form 3D network structure by the interactions of π-π stacking and hydrogen bonds. The Ca(II) complex catalyst could efficiently catalyse oxidation of benzylic alcohol with good conversion of benzyl alcohol (78 %) and excellent selectivity of benzaldehyde (98 %).